2021
DOI: 10.1089/jmf.2020.0137
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication with Ganoderma lucidum (“Reishi”) to Combat Parkinson's Disease Symptoms: A Single Case Study

Abstract: Parkinson's disease (PD) is a prevalent neurodegenerative disease for which only symptomatic treatments, mainly focused on motor symptoms. In contrast, conventional pharmacological treatments do not address cognitive impairment and emotional dysfunction. Together with potential treatment side effects, these can cause distress, lower the quality of life, and increase motor impairment in patients. Preclinical research suggests that the Traditional Chinese Medicine Ganoderma lucidum (“Reish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Study conducted by Sana et al (2021) shows that Ganoderma lucidium has neuroprotective and anti‐parkinsonian action on male Wistar rats against rotenone induced Parkinsonian affect 18 . A single case study of self‐medication of Ganoderma lucidium in which a 50‐year‐old male showed positive effects by improving motor skills, thought process, as well as emotion regulation, strengthens the clinical research findings 19 . Thus, GAA can be used for in vitro and vivo studies, which can lead to drug development of PD.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Study conducted by Sana et al (2021) shows that Ganoderma lucidium has neuroprotective and anti‐parkinsonian action on male Wistar rats against rotenone induced Parkinsonian affect 18 . A single case study of self‐medication of Ganoderma lucidium in which a 50‐year‐old male showed positive effects by improving motor skills, thought process, as well as emotion regulation, strengthens the clinical research findings 19 . Thus, GAA can be used for in vitro and vivo studies, which can lead to drug development of PD.…”
Section: Discussionmentioning
confidence: 69%
“… 18 A single case study of self‐medication of Ganoderma lucidium in which a 50‐year‐old male showed positive effects by improving motor skills, thought process, as well as emotion regulation, strengthens the clinical research findings. 19 Thus, GAA can be used for in vitro and vivo studies, which can lead to drug development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…A single case study involving self-medication with Ganoderma lucidum to combat Parkinson’s disease symptoms showed small positive changes in some facets of affective behavior. While this does not allow for firm conclusions, it suggests that clinical studies in this patient population may be warranted [ 141 ]. A randomized, double-blind, and placebo-controlled study of GLP in neurasthenia indicated that the extract was significantly superior to placebo in the clinical improvement of symptoms [ 142 ].…”
Section: Discussionmentioning
confidence: 99%